Breast injuries in women's sports: a scoping review of a female-specific sports injury - Dang, R.; Mattock, J. P. M.; McGhee, D. E. (Journal of Science and Medicine in Sport, 2025)
Objectives Breast injuries are female-specific injuries that occur in women's sports. Literature investigating this important women's breast health issue is scarce. This review aimed to collate and summarise published research on breast injuries in women's sports, highlighting the limitations and gaps in the literature.